Seftarolin, Antibiotik Baru dengan Aktivitas Anti-MRSA: Sebuah Kajian Efektivitas, Keamanan, dan Biaya Penggunaan : Ceftaroline, a New Anti-MRSA Antibiotic: a Review of the Efficacy, Safety, and Cost of Utilisation - Halim, Steven Victoria; Setiawan, Eko (Universitas Tadulako, 2020)
A growing problem in the medical field is the development of antibiotic resistant pathogens. One reason this development is so important is that in recent years there is a shortage of new antibiotics in development to combat resistant pathogens. It worths to mention that while 19 new antibiotics were released in the period 1980 to 1984, this had dropped to just three in the period 2005 to 2009. Ironically, the shortage of new antibiotics occur in the era where growing number of pathogens develop resistance to multiple antibiotics that previously effectively used to treat the infections. As a consequent, it is essential that the efficacy of last resort antibiotics, including the new antibiotics, be maintained as long as possible. Ceftaroline is a new antibiotic in Indonesia market which has methicillin-resistant Staphylococcus aureus activity and it belongs to the cephalosporins. Further understanding related to basic profile of ceftaroline, efficacy and safety, cost, and place in therapy is needed to optimize the responsible used of ceftaroline in daily medical practice